204k views
2 votes
One sixth of a number is 9 algebraic expression​

User Beanie
by
4.9k points

2 Answers

3 votes

Answer:

x= 54

Explanation:

let the number be (x)

so One sixth of x will be 9

numerically,

1/6 × (x) =9

x= 9×6

x= 54

User Lucius
by
4.7k points
10 votes

Given ↓

  • The verbal phrase → one-sixth of a number is 9

To find ↓

  • The algebraic expression of the verbal phrase

Calculations ↓

One-sixth can be written as
^1/_6

now, let the number be y

so one-sixth of y is written as


^1/_6~y~=~9

If it's necessary to solve for y, consult the [Solving for y] section of this ans ↓

[Solving for y]

First we need to get rid of the fraction, one-sixth.

since in mathematics we can't just terminate fractions without altering the equation/expression itself, we need to perform an operation.

the first one is multiplication; we will multiply both sides of the equation by 6 (the denominator of the fraction)


^1/_6*6~y~=~9~*~6}

On the left-hand side the 6's cancel, and we're left with

1 y = 9 * 6

Or

y = 9* 6

Which simplifies to :

y = 54

User Minchul
by
5.0k points